"Everyone thinks I am just lazy": Legitimacy narratives of Americans suffering from fibromyalgia. (January 2021) - Paxman, Christina G
This qualitative study reflects an analysis of 50 stories told by Americans living with fibromyalgia, a chronic condition marked by widespread physical pain. Stories were randomly collected from The Experience Project, an online public forum, and analyzed using the communication theory of identity as a guiding framework. Thematic analysis was used to examine how the legitimacy narratives of people with fibromyalgia respond to the American discourse of hard work. Three narrative themes emerged from the data: The Personal Experience of Living With Fibromyalgia (personal layer of identity), the Struggle to Complete Everyday and Professional Tasks (enacted layer of identity), and a Limited Ability to Perform Gender Roles (relational layer of identity). Throughout their stories, individuals with FM strive to legitimate their condition and contest the notion that they are lazy. Stories reveal that people suffering from fibromyalgia experience significant personal (e.g. cleaning the house) and professional (e.g. extended sick leave) challenges, as well as serious relational challenges that are often tied to gender roles (e.g. being a good mother). Results provide a variety of implications and directions for future research.